(untitled) (Journal of actual problems of jurisprudence, 2021)
The article has chosen the topic’s relevance because the «origin» of this organizational and legal form was in ancient times, even in Ancient Rome and Greece. In different traditional systems, such a corporate and legal structure as a Limited liability Partnership is called differently, so in England-a Limited Liability Partnership, in the United States of America – a Limited Liability Company, in Germany-a limited liability company. In this article, only some limited liability partnership elements will be analyzed using the comparative-legal method. In particular, we will talk about the number of participants, authorized capital, registration, liability, etc., in comparison with the Republic of Kazakhstan, England, the United States, and Germany. A business partnership is different from a simple partnership, which, according to article 228, has no authorized capital and is not a legal entity. In contrast to business partnerships, a simple partnership is formed based on a contract on joint activities of its participants, and the material basis of its activities is the property of the participants of a simple partnership, which is the common shared property of these participants, but not of the partnership. Keywords: civil Code, the Law on business partnerships, commercial organization, participants of business partnerships, comparative analysis of business partnerships.